Understanding the Current Financial Crisis - Kurniasih, Meutia (2009)
Financial markets suffered their one of the worst decline as the cost of borrowing for corporations continued to rise and some investors urged policymakers to help. Economists predicted that the tightening credit market would be a drag on the economy. Signs were emerging that the nation's credit problems were spreading in unpredicted ways due to the financial credit risk instruments used.